Alumina Heat Insulator Through Composite Poring Mechanisms. Issue 6 (11th June 2014) - Wu, Haibo; Huang, Zhengren; Wang, Gang; Li, Hongxia; Jiang, Dongliang
<x xml:space="preserve">Abstract</x> Crack‐free alumina heat insulators with large sizes were successfully prepared through composite poring mechanisms. In the sintered bodies, there existed 1–2 mm big pores due to solid template and 60–200 μm small pores due to direct foaming, and porosities (84.9–90.4%) were accurately tailored by varying the amounts of added polymer balls and foaming agent. Thanks to the excellent mechanical and thermal properties including compressive strengths of 2.3–5.2 MPa, thermal conductivity as low as 0.23 W/mK, and 50‐h creep strain of only 0.102% at 1200°C, they are potentially used as eco‐friendly substitutions for ceramic‐fiber insulators.